Active learning in criminal justice: The benefits of student investigation of wrongful convictions in a higher education setting. Issue 2 (1st June 2020) - Dealey, Jill
Abstract: Active learning, with students engaging in research or activities within the community, is a favoured approach in contemporary higher education. To support this approach, the Criminology and Forensic Studies programmes at the University of Winchester have included student research into miscarriages of justice. The students interrogate evidence from a criminal trial to attempt to establish if there has been a wrongful conviction. This article discusses the importance of this work for students of Criminology. It considers the contribution to the learning experience of the range of opportunities available to undergraduate and postgraduate students and evaluates the potential impact on curriculum and learning development during the degree programme, in addition to the benefits for future employment.